2019
DOI: 10.1177/0003319719840861
|View full text |Cite
|
Sign up to set email alerts
|

Nonhemostatic Activities of Factor Xa: Are There Pleiotropic Effects of Anti-FXa Direct Oral Anticoagulants?

Abstract: Factor Xa (FXa) is the key serine protease of the coagulation cascade as it is the point of convergence of the intrinsic and extrinsic pathways, leading to the formation of thrombin. Factor Xa is an established target of anticoagulation therapy, due to its central role in coagulation. Over the past years, several direct oral anticoagulants (DOACs) targeting FXa have been developed. Rivaroxaban, apixaban, and edoxaban are used in clinical practice for prevention and treatment of thrombotic diseases. Increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 101 publications
1
17
0
6
Order By: Relevance
“…18 Our data appear to show that apixaban is associated with approximately the same decrease in OR and improvement in survival as prophylactic enoxaparin, whether this is because of a similar AC effect or a similar anti-inflammatory effect is unknown at this point. 19,20 The strengths of this article are its large size and mature adjusted determination of baseline risk, establishing relevant variables and therapeutic intent in the first 48 hours. In addition, specific attention to medication type and dose adjusted to patient weight and creatinine clearance allowed us to establish AC therapeutic intent (prophylaxis or full therapy) prior to evaluating the impact of that intent on downstream mortality.…”
Section: Discussionmentioning
confidence: 99%
“…18 Our data appear to show that apixaban is associated with approximately the same decrease in OR and improvement in survival as prophylactic enoxaparin, whether this is because of a similar AC effect or a similar anti-inflammatory effect is unknown at this point. 19,20 The strengths of this article are its large size and mature adjusted determination of baseline risk, establishing relevant variables and therapeutic intent in the first 48 hours. In addition, specific attention to medication type and dose adjusted to patient weight and creatinine clearance allowed us to establish AC therapeutic intent (prophylaxis or full therapy) prior to evaluating the impact of that intent on downstream mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Most clinical studies demonstrated that targeting Factor Xa inhibition with NOAC including rivaroxaban prevented systemic thromboembolic disease, reduced cardiovascular events, and death [ 60 ]. Moreover, NOAC non-hemostatic cellular effects suggest a potential benefit in inflammation, arterial stiffness, neointima formation, atherosclerosis, and fibrosis [ 5 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation plays a key role in cardiovascular disorders [ 1 ] and interfering with coagulation factors represents one of the main pharmacological approaches in CVD [ 2 ]. Coagulation factors, not only participate to the activation of the coagulation cascade but also impact vascular function; this is the case for factor X (FXa), one of the main components in the coagulation process [ 3 ], which, through the activation of protease-activated receptors (PAR) [ 4 ], affects, vasomotor responses, inflammation, endothelial function, vascular proliferation, cellular hypertrophy, atherosclerosis, and thrombosis [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…pleio -множественный и tropos -действие) препарата называют множественность его эффектов. Наряду с влиянием на гемостаз обнаруживаются иные свойства антикоагулянтов, основными из которых при использовании прямых антикоагулянтов, в частности варфарина, являются воздействие на ангиогенез, противовоспалительное [8][9][10], антиатеросклеротическое [8,9], противоопухолевое [11,12] действия, угнетение процессов ремоделирования предсердий [8,9] и влияние на почки [13,14]. В настоящее время изучен далеко не весь спектр плейотропных эффектов антикоагулянтов.…”
Section: плейотропные эффекты антикоагу лянтов и пути их реализацииunclassified
“…После активации рецепторов FXa инициируется гидролиз фосфатидилинозитола, который приводит к изменению содержания внутриклеточного кальция. FXa также инициирует фосфорилирование митоген-активированных протеинкиназ [8], что приводит к запуску различных транскрипционных программ. Эти программы способствуют росту и дифференцировке клеток, а также индукции генов, кодирующих цитокины (интерлейкин (ИЛ)-6, ИЛ-8, моноцитарный хемотаксический фактор-1, тканевой фактор, молекулы межклеточной адгезии-1) и белки внеклеточного матрикса (фактор роста соединительной ткани, коллаген, фибронектин).…”
Section: плейотропные эффекты антикоагу лянтов и пути их реализацииunclassified